GV6029A: a new vitamin A biofortified maize variety in Zambia - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, 27 new varieties of vitamin A banana/plantain, cassava, maize, and sweet potato; iron beans, cowpea, and pearl millet; zinc rice, maize, and wheat were released. Evidence provided links to the biofortification crops map. An internal HarvestPlus database along with breeding reports can be made available upon request.